Strategies for activity maintenance in patient and family care and clinical trial adherence of GNA social plan in context of COVID‐19 health emergency. (December 2021) - Andrade‐Villegas, Angela M; Aguillon, David; Gómez, Manuela; Gómez‐Henck, Clara; Zuluaga, Maria; Rassi, Sofia; Ramos, Claudia; Madrigal, Claudia; Uribe, Claramonika; Saldarriaga, Amanda; Alzate, Diana; Ruiz, Alejandra; et al.
Abstract: Background: The current pandemic COVID‐19 caused by SARS‐CoV2 has become a public health challenge, causing difficulty in patient care and follow up of people with cognitive impairment due to Alzheimer's disease. This situation motivated changes and adjustments to the Group of Neurosciences of Antioquia's (GNA) Social Plan to guarantee effective continuity in patient care, family follow‐up, community interventions and adherence to the Alzheimer's Prevention Initiative (API) Colombia clinical trial. This was an opportunity to innovate, create, reinvent and expand forms of care and intervention during confinement and pandemic to promote access through virtual media and the well‐being of beneficiaries. Methods: The Social Plan program involves free access to basic care supplies for patients, home‐visits, support groups, cognitive stimulation groups and virtual community outreach activities like workshops for caregivers/interested public, Alzheimer's Day Commemoration "Cuidarme – Cuidarte" event (with available recorded resources), symposiums for caregivers, and informative meetings with participants of the API Colombia clinical trial. Results: In the period of mandatory preventive confinement, 30 families obtained diapers, 23 families received prescription drugs not provided by health maintenance organizations (HMO) and 48 families received groceries. A total of 32 home‐visits were made: 7 in rural areas and 25 in urban areas. At the end of the mandatory preventive confinement, outpatient medical consults were resumed, no participants withdrew from the trial during this period. Thirty‐six people with MCI or dementia participated in virtual cognitive stimulation activities. Caregiver remote workshops held in the first semester of 2020 had a total attendance of 80 people, and events held in the second semester, such as the Commemoration of Alzheimer's Day and the Symposium for Caregivers, had a total attendance of 1, 665 people and 1, 000 people respectively. Conclusion: GNA's Social Plan and the amended which includes strategies of social support, knowledge and patient/caregiver empowerment strengthened the interaction between the community and GNA and likely favorably influenced adherence and retention in the API Colombia clinical trial in the face of challenges from the global pandemic.